Chronology and documentary handbook of the State of Louisiana - Vexler, Robert I. (Chronologies and documentary handbooks of the states, 1978)
Contains a chronology of historical events from 1519 to 1977, a biographical directory of prominent citizens, and copies of pertinent documents.